Release film and transfer film

The use of a diamond-like carbon release layer with specific optical properties addresses the peeling force and heat resistance issues of conventional copper foils, enabling easy and heat-resistant separation from copper layers in transfer films.

JP2025012479APending Publication Date: 2025-01-24OIKE & CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023115338
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional copper foils with release films lack appropriate peeling force and heat resistance, particularly when exposed to heat loads in atmospheric conditions.

Method used

A release film and transfer film configuration utilizing a diamond-like carbon (DLC) release layer with specific refractive index, extinction coefficient, and surface properties, allowing for easy peelability and heat resistance, even in atmospheric processes.

Benefits of technology

The DLC release layer provides excellent releasability and heat resistance, ensuring easy separation from copper layers even under heat loads, enhancing the suitability of the film as a release layer in transfer films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012479000001_ABST
    Figure 2025012479000001_ABST
Patent Text Reader

Abstract

To provide a release film that exhibits thermal resistance applicable even to processes under thermal loads within atmospheric environment, wherein the release film serves as a suitable release layer with light peelability for transfer film applications, as well as to provide a transfer film.SOLUTION: A release film has a substrate and a peeling layer in the stated order. The peeling layer contains diamond-like carbon. The refractive index n of the peeling layer at a wavelength of 550 nm is 1.92 to 2.25. The extinction coefficient k of the peeling layer at a wavelength of 550 nm is 0.159 to 0.792.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film and a transfer film. More specifically, the present invention relates to a release film and a transfer film that have heat resistance applicable even in a process that is subjected to a thermal load, and that are suitable as a release layer having light releasability when used in a transfer film. [Background technology]

[0002] Conventionally, a copper foil with a release film having a structure of film / release layer / copper layer has been developed as a transfer film with a release film (Patent Document 1). In the copper foil with a release film of Patent Document 1, the thickness of the copper layer is 0.5 to 3.0 μm, and the surface of the copper layer contains crystal grains of 5 to 50 nm at an area ratio of 65% or more. It is also disclosed that in the copper foil with a release film of Patent Document 1, the release layer can be a carbon layer having a thickness of 0.5 to 5.0 nm. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-30350 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the copper foil described in Patent Document 1 does not have a peel strength suitable for use as a release layer for a transfer film. In particular, the copper foil described in Patent Document 1 is limited to thermal load in a vacuum or reducing atmosphere, and does not have heat resistance suitable for use in processes in which thermal load is applied in the atmosphere.

[0005] The present invention has been made in consideration of such conventional inventions, and aims to provide a release film and a transfer film that have heat resistance applicable even in processes that are subjected to thermal load in the atmosphere, and that are suitable as a release layer with easy peeling properties when used in a transfer film. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by adopting a release layer containing diamond-like carbon as the release layer formed on the substrate and adjusting the refractive index and extinction coefficient of the release layer to be within a specific range, and have completed the present invention. That is, the release film and transfer film of the present invention that solve the above-mentioned problems mainly include the following configurations.

[0007] (1) A release film comprising a substrate and a release layer in this order, the release layer containing diamond-like carbon, the release layer having a refractive index n of 1.92 to 2.25 at a wavelength of 550 nm, and an extinction coefficient k of 0.159 to 0.792 at a wavelength of 550 nm.

[0008] According to this configuration, the release film has heat resistance that allows it to be used in processes in which heat load is applied in the atmosphere. Furthermore, when the release film is used for a transfer film, it has light releasability and is suitable as a release layer.

[0009] (2) The release film according to (1), wherein the surface of the release layer has a contact angle with pure water of 34 to 77°.

[0010] According to this configuration, when a copper layer is provided on the release layer, the release film has excellent releasability from the copper layer.

[0011] (3) The release film according to (1) or (2), wherein the half-value width of the graphite component in Raman spectroscopic analysis of the release layer is 137.0 to 162.4.

[0012] According to this configuration, when a copper layer is provided on the release layer, the release film has excellent releasability from the copper layer.

[0013] (4) The release film of any of (1) to (3), further comprising a copper layer having a thickness of 108 to 122 nm formed by sputtering on the release layer, and after a heat treatment is performed for 90 minutes in an atmosphere at 180° C. under atmospheric pressure, the 180-degree peel force between the release layer and the copper layer at a speed of 50 mm / min is 34 N / m or less.

[0014] According to such a configuration, the release film has excellent releasability from the copper layer even when a copper layer is provided on the release layer in a process that is subjected to a thermal load.

[0015] (5) A transfer film comprising the release film according to any one of (1) to (4) above and a copper layer formed on the release film.

[0016] According to this configuration, the transfer film has excellent peelability from the copper layer even when the copper layer is provided in a process that is subject to a thermal load. Effect of the Invention

[0017] According to the present invention, it is possible to provide a release film and a transfer film that have heat resistance suitable for use in processes that are subjected to thermal load in the atmosphere, and that are suitable as a release layer with easy peeling properties when used in a transfer film. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view of a release film and a transfer film according to one embodiment of the present invention (first embodiment). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Release film> The release film of one embodiment of the present invention has a substrate and a release layer in this order. The release layer contains diamond-like carbon (hereinafter also referred to as DLC). The release layer has a refractive index n of 1.92 to 2.25 at a wavelength of 550 nm. The release layer has an extinction coefficient k of 0.159 to 0.792 at a wavelength of 550 nm. Each configuration will be described below.

[0020] Fig. 1 is a schematic cross-sectional view of a release film 1 of the present embodiment and a transfer film 10 described later. As shown in Fig. 1, the release film 1 has a base material 2 and a peeling layer 3 in this order. Note that reference numeral 4 denotes a copper layer provided in the transfer film 10 described later.

[0021] ·Base material The substrate is not particularly limited. For example, the substrate is a fluororesin film (PTFE film, PFA film, etc.), an LCP film, a PI film, a transparent PI film, an MPI film, a COP film, a polyester film, an olefin film, etc. Among these, the substrate is preferably a PET film, a PTFE film, a transparent PI film, or an LCP film, and more preferably a PET film.

[0022] The substrate may contain known additives such as antistatic agents, ultraviolet absorbers, plasticizers, lubricants, colorants, etc. The substrate may also be coated in advance on one or both sides with a resin layer such as a silane coupling agent, acrylic, polyester, or epoxy.

[0023] The thickness of the substrate is not particularly limited. For example, the thickness of the substrate is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 12 μm or more. The thickness of the substrate is preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 75 μm or less. By having the thickness of the substrate within the above range, the release film has a good balance between flexibility and rigidity, is easily adapted to fine irregularities during transfer, and has durability and heat resistance, making it easy to handle and allowing a wide range of material selection.

[0024] Peeling layer The release layer of this embodiment contains diamond-like carbon (DLC). DLC refers to an amorphous hard film mainly composed of hydrocarbons or carbon allotropes. DLC has a structure in which both diamond bonds (SP3 bonds) and graphite bonds (SP2 bonds) are mixed.

[0025] The method for forming DLC ​​is not particularly limited. As an example, DLC can be formed by a method in which plasma pretreatment is performed using DC sputtering or high-voltage pulse sputtering, and film formation is performed using magnetron sputtering.

[0026] DC sputtering supplies a direct current to excite the target to form plasma. On the other hand, high-pressure pulse sputtering uses pulse waves to form very high-density plasma, so sputtering is performed at a high power density, improving the ionization rate of the sputtered particles of the target material, and enabling the formation of a higher quality thin film. In the release film of this embodiment, high-pressure pulse sputtering is used when forming DLC, so that the ionization rate of carbon in DLC is increased, and even if a copper layer is provided on the release layer, the release film has excellent peelability from the copper layer.

[0027] The content of DLC in the release layer is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. On the other hand, the content of DLC in the release layer may be 100% by mass. That is, the release layer may be composed of DLC itself. By the content of DLC being within the above range, the release film has heat resistance applicable even in a process in which a thermal load is applied in the atmosphere. In addition, when the release film is used for a transfer film, it has light releasability and is suitable as a release layer. In addition, when the release layer contains components other than DLC, the components other than DLC are hydrogen, oxygen, nitrogen, metal, etc. In addition, in this embodiment, the release layer may contain impurities that are inevitably contained.

[0028] The refractive index n of the release layer at a wavelength of 550 nm may be 1.92 or more, preferably 1.95 or more, and more preferably 2.00 or more. The refractive index n may be 2.25 or less, preferably 2.20 or less, and more preferably 2.15 or less. When the refractive index n is less than 1.92, the release film may contain a large amount of impurities such as hydrogen in the DLC, and the release property becomes heavy. On the other hand, when the refractive index n is more than 2.25, the hardness of the release layer of the release film becomes too high, the flexibility is lost, and cracks are easily generated without the ability to follow the support film, making handling difficult. In the release film of this embodiment, the refractive index n is 1.92 or more, so that the film density is high, the film itself is stabilized by physical and chemical interactions, and it is difficult to bond with other substances, and it is considered that the release film can be easily peeled off. In this embodiment, the refractive index n and the extinction coefficient k described later can be measured using a spectroscopic ellipsometer (UVISEL2, xenon lamp light source, manufactured by Horiba) with a measurement wavelength of 190 nm to 2100 nm, a spot diameter of 2030 μm × 705 μm ellipse, and an incidence angle of 70°.

[0029] In addition, the extinction coefficient k of the release layer at a wavelength of 550 nm may be 0.159 or more, preferably 0.200 or more, and more preferably 0.300 or more. In addition, the extinction coefficient k may be 0.792 or less, preferably 0.700 or less, and more preferably 0.650 or less. When the extinction coefficient k is less than 0.159, the release film has a large amount of hydrogen components in the film, and the number of hydroxyl groups (-OH groups) on the film surface increases, increasing adhesion, and impairing easy releasability. On the other hand, when the extinction coefficient k is more than 0.792, the release film has DLC graphitized, the film surface becomes rough, and the anchor effect becomes apparent, impairing easy releasability. In the release film of this embodiment, since the extinction coefficient k is within the above range, the hydrogen content in the DLC is sufficient to form a polymer component, and the polymer component fills the DLC microcrystal grain boundaries, thereby exhibiting oxygen barrier properties and preventing oxidation of the transfer material (copper, aluminum, etc.) formed on the release layer when heated in the atmosphere. As a result, it is believed that the release film is less susceptible to deterioration in releasability.

[0030] The pure water contact angle of the surface of the release layer is preferably 34° or more, more preferably 40° or more. The pure water contact angle is preferably 77° or less, more preferably 65° or less. When the pure water contact angle is within the above range, the release film has excellent peelability from the copper layer when a copper layer is provided on the release layer. In this embodiment, the contact angle of the surface of the release layer can be measured using a contact angle measuring device (DROPMASTER500, Kyowa Interface Science Co., Ltd.), liquid diameter: 1.5 mm, measurement environment: temperature 23° C., humidity 65% ​​RH, measurement method: five drops of the dripped liquid are dropped on the surface of the DLC release layer, the contact angle after 10 seconds is measured, and the average value of the three contact angles excluding the maximum and minimum values ​​is calculated.

[0031] The surface roughness (Ra) of the release layer is preferably 0.10 μm or more, more preferably 0.15 μm or more. The surface roughness (Ra) of the release layer is preferably 0.30 μm or less, more preferably 0.25 μm or less. By having the surface roughness (Ra) of the release layer within the above range, the release film can avoid an area where the adhesive force is strong due to the anchor effect caused by the surface roughness being increased, resulting in poor releasability, due to the atomic interaction caused by the surface smoothness being too good, or the surface roughness being too rough. In this embodiment, the surface roughness (Ra and Rz described later) can be measured using an ultra-deep shape measuring microscope (VK-9510 GII, Keyence) under conditions of a violet laser (wavelength 408 nm), a magnification of 50 times, and an objective lens with a numerical aperture of 0.95.

[0032] The surface free energy of the peeling layer is 45.0 (gL / mN m -1 ) or more, and 50.0 (gL / mN m -1 ) or more. The surface free energy of the release layer is preferably 65.0 (gL / mN m -1 ) or less, and 60.0 (gL / mN m -1 ) or less is more preferable. By having the surface free energy of the release layer within the above range, the release film does not peel too hard to make transfer difficult, and does not peel too lightly to cause the transfer foil to peel off from the support during handling. In this embodiment, the surface free energy can be calculated using a contact angle meter (DROPMASTER500, Kyowa Interface Science Co., Ltd.) by deriving the measured values ​​of the pure water contact angle, diiodomethane contact angle, and a-bromonaphthalene contact angle from Young's equation.

[0033] Furthermore, the fact that the release layer contains DLC can be confirmed by performing Raman spectroscopy on the release layer. That is, by preparing a single release layer (a sample in which only the release layer is formed on a silicon wafer) and performing Raman spectroscopy (excitation wavelength 532 nm, objective lens 20x, numerical aperture NA=0.45, slit width 50 μm), not only the graphite peak but also the diamond peak can be observed. This makes it possible to confirm that the release layer is a DLC film.

[0034] The half-width of the graphite component (G component) in the Raman spectroscopic analysis of the release layer is preferably 137.0 or more, more preferably 140.0 or more. The half-width of the G component is preferably 162.4 or less, more preferably 160.0 or less. When the half-width of the G component is within the above range, the release film has excellent peelability from the copper layer when a copper layer is provided on the release layer.

[0035] The thickness of the release layer is not particularly limited. For example, the thickness of the release layer is preferably 0.5 nm or more, more preferably 1 nm or more, and even more preferably 5 nm or more. The thickness of the release layer is preferably 60 nm or less, more preferably 35 nm or less, and even more preferably 25 nm or less. When the thickness of the release layer is within the above range, the release film has good transferability, and is excellent in productivity and workability. The thickness of the release layer can be measured by a stylus type using a step gauge (step / surface roughness shape measuring instrument, P-6, manufactured by KLA-Tencor JAPAN Co., Ltd.) with a scanning distance of 60 mm and a measurement range of approximately 10 nm to 300 μm.

[0036] The release layer may be provided directly on the substrate, or may be provided with other layers sandwiched therebetween. Fig. 1 illustrates an embodiment in which the release layer is provided directly on the substrate. Such other layers include, for example, various metal layers and various resin layers.

[0037] The metal of the metal layer is, for example, copper, aluminum, silver, gold, palladium, titanium, nickel, nickel alloy (nickel-copper alloy, nickel-chromium alloy, nickel-copper-titanium alloy, nickel-chromium-titanium alloy, etc.), etc. The metal layer may be a multi-layer structure.

[0038] When the metal layer is provided, the thickness of the metal layer is not particularly limited. For example, the thickness of the metal layer is preferably 20 nm or more, more preferably 30 nm or more. The thickness of the metal layer is preferably 200 nm or less, more preferably 100 nm or less. By having the thickness of the metal layer within the above range, the release film can obtain electrical conductivity, and electrolytic plating can be performed on the release layer.

[0039] The resin of the resin layer is, for example, an acrylic resin, a urethane resin, a polyester resin, a melamine resin, an epoxy resin, a siloxane resin, a fluorine resin, etc. The resin layer may be a multi-layered layer.

[0040] When the resin layer is provided, the thickness of the resin layer is not particularly limited. For example, the thickness of the resin layer is preferably 100 nm or more, more preferably 500 nm or more. The thickness of the resin layer is preferably 3 μm or less, more preferably 1 μm or less. By having the thickness of the resin layer within the above range, the flexibility of the release layer of the release film is improved, the handling is facilitated, and the use applications are expanded.

[0041] In addition, a metal layer and a resin layer may be laminated between the substrate and the release layer.

[0042] The release film of the present embodiment can be used as a transfer film having excellent releasability from the copper layer by further forming a copper layer on the release layer.

[0043] Copper layer The copper layer is provided on the release layer. The method for providing the copper layer is not particularly limited. For example, the copper layer can be provided by sputtering, plating, or the like.

[0044] When the copper layer is formed by sputtering, the thickness of the copper layer is preferably 108 nm or more, more preferably 110 nm or more. The thickness of the copper layer is preferably 122 nm or less, more preferably 120 nm or less. When the thickness of the copper layer formed by sputtering is within the above range, the release film has excellent peelability from the copper layer even when the copper layer is provided on the peeling layer in a process where a thermal load is applied. The thickness of the copper layer can be measured from an XRF calibration curve using a tabletop wavelength dispersive X-ray fluorescence analyzer (Primini, manufactured by Rigaku Corporation).

[0045] In addition, when the copper layer is formed by sputtering, the 180-degree peeling force between the release layer and the copper layer at a speed of 50 mm / min after 90 minutes of heat treatment in an atmosphere of 180° C. under atmospheric pressure is preferably 34 N / m or less, more preferably 30 N / m or less. In addition, the 180-degree peeling force is preferably 5 N / m or more, more preferably 7 N / m or more. By having the peeling force within the above range, the release film has excellent peelability from the copper layer even when a copper layer is provided on the release layer in a process in which a thermal load is applied. In this embodiment, the peeling force can be measured using a peel strength tester (autograph tensile tester, AGS-100G, manufactured by Shimadzu Corporation). At that time, heating can be performed by an oven. For example, a thermostatic dryer (OFW-450, manufactured by AS ONE Corporation) can be used as the oven.

[0046] The copper content in the copper layer is not particularly limited. For example, the copper content is preferably 95% by mass or more, more preferably 99% by mass or more, and even more preferably 99.8% by mass or more. Copper may be 100% by mass in the copper layer. That is, the copper layer may be composed of copper itself. In this embodiment, the copper layer may contain impurities that are inevitably contained therein.

[0047] Furthermore, the copper layer may contain Al, Ni, Zn, Sn, Ti, and the like in addition to copper (Cu).

[0048] As described above, the release film of the present embodiment has heat resistance that allows it to be used in processes that involve thermal loads. Furthermore, when the release film is used in applications such as transfer films, it has light releasability and is suitable as a release layer.

[0049] <Transfer film> The transfer film of one embodiment of the present invention includes the above-mentioned release film and a copper layer formed on the release film. Each of them will be described below. In the following description, the matters described above in relation to the release film will be omitted as appropriate.

[0050] 1, the transfer film 10 includes a copper layer 4 provided on a release film 1. The copper layer 4 can be provided by sputtering, plating, etc., as described above in relation to the embodiment of the release film 1.

[0051] The transfer film of this embodiment is pressed against a substrate via the adhesive layer, and then peeled off at the interface between the copper layer and the release layer, thereby transferring the copper layer to the substrate.

[0052] Specifically, first, an adhesive layer is formed on the copper layer of the transfer film. The adhesive layer is not particularly limited. For example, the adhesive for forming the adhesive layer is an acrylic adhesive, a urethane adhesive, an ester adhesive, an epoxy adhesive, a silicone adhesive, or the like. These adhesives are applied to the surface of the copper layer by any coating method and dried.

[0053] The thickness of the adhesive layer is not particularly limited, and is, for example, 0.05 to 5.0 μm.

[0054] The transfer can be performed by attaching the adhesive layer to a substrate and using a roll transfer machine or the like. The substrate is not particularly limited. Examples of the substrate include PET (polyester), PT (cellophane), PE (polyethylene), PLA (polylactic acid), and PBS (polybutylene succinate).

[0055] The thickness of the transfer substrate is not particularly limited, and is, for example, 12 to 75 μm.

[0056] As described above in relation to the embodiment of the release film, the transfer film of this embodiment can have a 180-degree peel force between the release layer and the copper layer at a speed of 50 mm / min of 34 N / m or less after 90 minutes of heat treatment in an atmosphere of 180° C. under atmospheric pressure. Therefore, the transfer film has excellent peelability from the copper layer even when a copper layer is provided on the release layer in a process that applies a thermal load. EXAMPLES

[0057] The present invention will be described in more detail below with reference to the following examples. The present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass".

[0058] <Example 1> A PET film (thickness 50 μm) was used as a substrate, and a release layer (thickness 22 nm) made of DLC was formed on the substrate by DC magnetron sputtering a carbon target in an Ar atmosphere. Next, a copper layer (thickness 111 nm) was formed on the release layer by DC magnetron sputtering a copper target in an Ar atmosphere. The thickness of the release layer was measured using a step gauge (step / surface roughness shape measuring instrument, KLA-Tencor JAPAN, P-6) with a stylus type scanning distance of 60 mm and a measurement range of approximately 10 nm to 300 μm. The thickness of the copper layer was measured from an XRF calibration curve using a tabletop wavelength dispersive X-ray fluorescence analyzer (Primini, Rigaku). Furthermore, confirmation that the release layer was a DLC film was performed using a laser Raman microscope. That is, a single release layer (a sample in which only the release layer was formed on a silicon wafer) was prepared and subjected to Raman spectroscopy (excitation wavelength 532 nm, objective lens 20x, numerical aperture NA=0.45, slit width 50 μm). Not only graphite peaks but also diamond peaks were observed, confirming that the release layer was a DLC film.

[0059] <Examples 2 to 8, Comparative Examples 1 to 2> A release film and a transfer film were produced in the same manner as in Example 1, except that the formulation and conditions were changed to those shown in Table 1.

[0060] [Table 1]

[0061] The obtained release film and transfer film were evaluated by the following methods to determine the optical constants (refractive index n and extinction coefficient k), Raman spectroscopy, surface roughness (Ra and Rz), contact angle (°), and surface free energy (gL / mNm -1 ), dispersion force (gLd / mNm -1 ), polarity (gLp / mNm -1 ), hydrogen bonds (gL / mNm -1The results are shown in Table 3.

[0062] <Optical constants (refractive index n and extinction coefficient k)> A spectroscopic ellipsometer (Horiba, UVISEL2, xenon lamp light source) was used, and measurements were performed at a measurement wavelength of 190 nm to 2100 nm, a spot diameter of 2030 μm×705 μm ellipse, and an incident angle of 70°. <Raman spectroscopy> Measurements were made using a laser Raman microscope (model number RAMAN touch, manufactured by Nanophoton). <Surface roughness> The surface roughness was measured using a depth profile measuring microscope (VK-9510 GII, Keyence) under the conditions of a violet laser (wavelength 408 nm), a magnification of 50, and an objective lens with a numerical aperture of 0.95. <Contact angle (°)> (pure water) The contact angle was measured using a contact angle measuring device (DROPMASTER500, Kyowa Interface Science Co., Ltd.) with a liquid diameter of 1.5 mm, measurement environment: temperature 23°C, humidity 65% ​​RH, and measurement method: 5 drops of the liquid were dropped onto the surface of the DLC peeling layer, the contact angle was measured after 10 seconds, and the average value of the contact angles of the 3 points excluding the maximum and minimum values ​​was calculated. (Diiodomethane) The contact angle was measured using a contact angle measuring device (DROPMASTER500, Kyowa Interface Science Co., Ltd.) with a liquid diameter of 1.5 mm, measurement environment: temperature 23°C, humidity 65% ​​RH, and measurement method: 5 drops of the liquid were dropped onto the surface of the DLC peeling layer, the contact angle was measured after 10 seconds, and the average value of the contact angles of the 3 points excluding the maximum and minimum values ​​was calculated. (a-Bromonaphthalene) The contact angle was measured using a contact angle measuring device (DROPMASTER500, Kyowa Interface Science Co., Ltd.) with a liquid diameter of 1.5 mm, measurement environment: temperature 23°C, humidity 65% ​​RH, and measurement method: 5 drops of the liquid were dropped onto the surface of the DLC peeling layer, the contact angle was measured after 10 seconds, and the average value of the contact angles of the 3 points excluding the maximum and minimum values ​​was calculated. <Surface free energy (gL / mNm -1 )> The surface free energy was measured using a contact angle meter (DROPMASTER500, Kyowa Interface Science Co., Ltd.) by substituting the measured values ​​of the pure water contact angle, diiodomethane contact angle, and a-bromonaphthalene contact angle into Young's equation. <180 degree peel force between release layer and copper layer (N / m), peeling residue after peeling (visual observation)> The peel strength was measured using a peel strength tester (autograph tensile tester, AGS-100G, manufactured by Shimadzu Corporation) for each sample immediately after preparation (initial stage) and after heat treatment at 180°C for 90 minutes in air. Heating was performed in an oven. The oven used was a thermostatic dryer (OFW-450, manufactured by AS ONE Corporation). After that, the presence or absence of peeled off residue after peeling was visually observed.

[0063] [Table 2]

[0064] [Table 3]

[0065] As shown in Tables 2 and 3, the release films and transfer films of the examples of the present invention both had small peel strength after treatment at 180°C for 90 minutes in air, and had heat resistance that was applicable even in processes that involved heat loads. In addition, the transfer films of the examples of the present invention had light peelability and no peel residue.

[0066] In the above examples, the transfer film includes a release film and a copper layer formed on the release film, and the transfer film has excellent releasability at the interface between the release layer and the copper layer (especially in the atmosphere after a thermal load is applied). However, as a result of detailed investigation by the present inventor, it was found that the easy releasability in the atmosphere after a thermal load is not limited to the copper layer, and similar easy releasability can be obtained with an aluminum layer. In other words, it was confirmed that the release film of the present invention has excellent heat-resistance releasability not only for the copper layer but also for the aluminum layer. [Explanation of symbols]

[0067] 1 Release film 2 Base material 3. Peel layer 4 Copper Layer 10 Transfer film

Claims

1. A substrate and a release layer in this order, the release layer includes diamond-like carbon; The release layer has a refractive index n of 1.92 to 2.25 at a wavelength of 550 nm; The release layer has an extinction coefficient k of 0.159 to 0.792 at a wavelength of 550 nm.

2. 2. The release film according to claim 1, wherein the surface of the release layer has a contact angle with pure water of 34 to 77°.

3. 3. The release film according to claim 1, wherein the half-value width of the graphite component in Raman spectroscopy of the release layer is 137.0 to 162.

4.

4. A copper layer having a thickness of 108 to 122 nm is formed on the release layer by sputtering, 3. The release film according to claim 1, wherein the 180-degree peel force between the release layer and the copper layer at a speed of 50 mm / min after 90 minutes of heat treatment in an atmosphere at 180° C. under atmospheric pressure is 34 N / m or less.

5. A transfer film comprising the release film according to claim 1 or 2 and a copper layer formed on the release film.

Citation Information

Patent Citations

  • Copper foil with release film and method for manufacturing copper foil with release film

    JP2017030350A